2017
DOI: 10.1017/s0007114517000290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-month intervention with lipid-based nutrient supplement on the physical activity of Malawian toddlers: a randomised, controlled trial

Abstract: Physical activity is beneficial for children’s well-being. The effect of dietary supplementation on children’s physical activity in food-insecure areas remains little studied. We examined the effects of a lipid-based nutrient supplement (LNS) on children’s objectively measured physical activity in a randomised, controlled, outcome-assessor-blinded trial. Mothers of the children received one capsule daily of Fe-folic acid (IFA), one capsule containing eighteen micronutrients (MMN) or one 20 g sachet of LNS (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Studies were conducted in 16 different countries, including 8 in the United States [36][37][38][39][40][41][42][43], 4 in Canada [29,[44][45][46] and Australia [23,24,47,48], 2 in China [28,49] and Sweden [26,28], and 1 in Belgium [26], Estonia [26], Germany [26], Hungary [26], Italy [26], Malawi [50], the Netherlands [27], New Zealand [25], Spain [26], Switzerland [33], and Taiwan [51] (note that one study was conducted in both China and Sweden [28] and one study was conducted in Belgium, Estonia, Germany, Hungary, Italy, Spain, and Sweden [26]). The mean sample size of included studies was 142 children (range = 7 to 568), and all studies were published in 2011 or later (88% since 2015).…”
Section: Study Characteristics and Quality Of Included Articlesmentioning
confidence: 99%
“…Studies were conducted in 16 different countries, including 8 in the United States [36][37][38][39][40][41][42][43], 4 in Canada [29,[44][45][46] and Australia [23,24,47,48], 2 in China [28,49] and Sweden [26,28], and 1 in Belgium [26], Estonia [26], Germany [26], Hungary [26], Italy [26], Malawi [50], the Netherlands [27], New Zealand [25], Spain [26], Switzerland [33], and Taiwan [51] (note that one study was conducted in both China and Sweden [28] and one study was conducted in Belgium, Estonia, Germany, Hungary, Italy, Spain, and Sweden [26]). The mean sample size of included studies was 142 children (range = 7 to 568), and all studies were published in 2011 or later (88% since 2015).…”
Section: Study Characteristics and Quality Of Included Articlesmentioning
confidence: 99%
“…A more recent systematic review of longitudinal observational studies and controlled trials conducted in 2016 showed that predictors of increased physical activity in 0–6 year olds included parental monitoring of their children’s activity, maternal role modeling; and there was some inconsistent evidence that boys had higher physical activity than girls [ 14 ]. This systematic review reported that very few studies had been conducted in healthy children under age two, or in developing countries (with none conducted in Africa), however recently studies have been conducted measuring physical activity response to dietary treatment or supplementation in undernourished toddlers in Africa [ 15 , 16 ]). Studies on infants and toddlers have consistently shown age to be associated with increased sedentary behaviour and with more time spent in higher intensity physical activity [ 17 – 20 ], yet it is likely that developmental stage (rather than chronological age) will impact on ability to participate in certain types and intensities of activity, thus presenting a bidirectional relationship between developmental stage and physical activity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the postnatal supplementation trial, there were no significant effects of 10-to 40-g quantities/ d of LNS provided from 6 to 18 months of age on PA outcomes at 18 months (25) . The prenatal and postnatal supplementation study in Malawi (26) was conducted in parallel with the trial in Ghana described here and had the same intervention groups and design. In Malawi, no differences were found between the LNS, MMN and IFA groups in any PA outcomes measured at 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…In response to low dietary intakes of energy and protein, undernourished children exhibit behavioural changes including reduced PA and exploration in their environment (15) , which may persist into adolescence (13) . Deficiencies in micronutrients, particularly Fe (16)(17)(18) and Zn (19,20) , are associated with reduced PA in early childhood; however, evidence for the effects of micronutrient supplementation during early life on behavioural PA in randomised trials has been mixed (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) , and only two such studies (25,26) have used accelerometers to measure PA outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation